The Effect of Coping Stress on Final Year Students' Academic Achievement Index - Oktara, Tri Windi; Murniasih, Farhanah; Rosida, Hilda (Kuras Institute, 2024)
Final year students often face significant academic and emotional challenges, especially when completing their theses, which can impact their academic performance. The aim of this research is to find out how coping with stress affects the academic achievement index of final year students. The sample of the study was 175 final year students who are doing their thesis of Universitas Islam Negeri Sultan Maulana Hasanuddin Banten. Data was collected through the Coping Stress questionnaire, the questionnaire revealed two aspects, namely problem-focused coping or coping focused on problems and emotion-focused coping or coping focused on emotions. The data analysis technique used in this research is linear regression. The results of the research show that stress coping for final year students has a significant effect on academic achievement. Besides that, there is a strong relationship between final year students' stress coping and academic achievement. Apart from that, coping stress in final year students has an effect on academic achievement by 36,1%. This study's findings highlight the importance of paying close attention to students' living situations, particularly those who reside with their parents. The emotional health and academic success of students can be improved when schools and parents work together to provide a nurturing atmosphere for them. The research show that stress coping for final year students has a significant effect on academic achievement.